ANALISIS PENGARUH HARGA DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN MEREK HANDPHONE (Studi Kasus Pada Konsumen Di Kota Parepare) - Herman (IAIN Parepare, 2024)
This research effort aims to find out how much influence price and product quality have on consumer decisions to buy cellphone brands in Parepare City. Apart from that, this research will analyze what factors have the most dominant influence in influencing consumers in buying cellphone brands, as well as what is considered important for consumers in these factors. The population in this study were all cellphone brand consumers in Parepare City who had decided to buy a cellphone brand. The sample used in this research was 50 people using an accidental sampling approach (taking samples by chance). The results of the initial analysis carried out show that the indicators used are valid for measuring existing variables. The results of the subsequent analysis found that of the three variables used in this research, price was the most dominant variable in influencing purchasing decisions. ABSTRAK